BUBUR SIMBUT SEBAGAI PERINTANG WARNA PADA KAIN DENGAN MENGGUNAKAN CANTING CAP - D. S., Bayu Wirawan; Rozaq, Abdul (JURNAL LITBANG KOTA PEKALONGAN, 2020)
Simbut fabric is part of history in the color barrier process that exists in Indonesia. Initially the sticking process of simbut porridge used glutinous rice porridge which was still warmly smeared with crushed bamboo stems. Dry glutinous rice porridge is easily cracked. The tool for applying it to cloth is still very simple. Because of that the decoration of simbut fabrics is also simple, not complicated. Therefore it is necessary to make research and innovation so that glutinous rice porridge (porridge simbut) is not easily cracked and can be applied with various tools. The purpose of this study was to apply simbut porridge, as a color barrier to the fabric using a wooden stamp canting. The method used is an experimental method. The experimental method is a study that seeks to find the effect of primary data applied to secondary data obtained under controlled conditions. The object of this research is glutinous rice porridge (simbut), where the attachment process uses wooden canting cap. From the results of the study, it was concluded that the simbut porridge could be used as a color barrier on the fabric by tasting technique. Keywords: Porridge simbut, Resist technique, Canting cap